Psychogenic diabetes insipidus – A case report of behavioral psychotherapy - Stanković, Miodrag M; Stevanović, Jelena; Stojanović, Aleksandra; Kostić, Jelena; Stanković, Sandra (Vojnosanitetski pregled, 2021)
Introduction. Psychogenic diabetes insipidus is potentially a life-threating condition manifesting as a psychogenic thirst disorder with excessive fluid intake (more than 3 L per day) and a preserved function of neurohypophysis and kidneys. Case report. We presented a boy aged 4 years and 8 months with symptoms of polydipsia, polyuria, nocturia and malnutrition. Pediatric examination and laboratory analysis were performed, but clear discrimination between psychogenic and nonpsychogenic diabetes insipidus could not be made. A psychiatric consultation was performed to examine the possibility of compulsive fluid taking. The differentiation was performed in two stages. In the first stage, the child was separated from the mother in short intervals. In the second stage, the behavioral psychotherapy interventions were performed: distraction of attention, and positive and negative reinforcement for delaying compulsive fluid taking. The mother was trained to use methods of operant conditioning, privilege and deprivation, as well as methods of exposure and response prevention and relaxation of the child. It was suggested to continue with multidisciplinary treatment (pediatric, liaison psychiatric and behaviour psychotherapeutic). Evaluation of behaviour therapy was performed after 4 and 12 weeks. During 4 weeks of follow-up, the boy reduced the daily fluid intake by 3.5 L, and added 1 kg of body weight. Also, intervals between fluid intake were significantly extended. This therapeutic effect could not be explained by the pediatric treatment introduced prior to the application of behaviour therapy and psychoeducation of the mother. Conclusion. Consultations and multidisciplinary approach by different health specialists in resolving of a number of predominantly somatic disorders in children with psychogenic diabetes insipidus should be highlighted as a way of treatment.